Beneficial Roles of Microglia and Growth Factors in MS, a Brief Review - Pons, Vincent; Rivest, Serge (Frontiers in Cellular Neuroscience, 2020)
Microglia are the brain resident immune cells; they can produce a large variety of growth factors to prevent neuronal damages and recovery. In neurodegenerative diseases, microglia are both benefic and deleterious depending on different factors and diseases. In multiple sclerosis, microglia are involved in both demyelination and remyelination processes. Recent studies suggest the beneficial role of microglia in regenerative processes. These include the regenerative development of myelin after demyelination. This review gives an overlook of how microglia and growth factors can influence the remyelination properties.